Urban Farming Competitiveness in Jakarta City in the Digital Era - M. Noor Salim; Darwati Susilastuti; Meita Novia; Elli Sulistyaningsih (GoAcademica Research & Publishing, 2023)
Urban farming farmers in Jakarta City, Indonesia are able to survive in the midst of increasing land conversion so that agricultural land is increasingly narrow. The strategy to increase the competitiveness of cultivation technology and digital technology is the main key to its development. The purpose of this study is to analyze the simultaneous and partial effects of competitiveness variables as measured by production, capital and labor on digital technology strategies and their impact on the income of urban farming MSMEs in Jakarta City. The survey research method uses OLS Multiple Regression data analysis techniques for urban farming farmers or MSMEs in the Jakarta City area. The results of the study are that simultaneously products, capital and labor have a positive effect on the strategy for determining digital technology. The competitiveness of capital and labor plays a positive role in determining digital technology, while products cannot compete and have no real effect. Digital technology strategies have a positive impact on farmers' income. The research finding is that urban farming in the city of Jakarta is able to compete with the determining factor being its human resources in implementing digital technology in its farming. Without the application of digital technology will reduce income.